2017
DOI: 10.1186/s12986-017-0229-8
|View full text |Cite
|
Sign up to set email alerts
|

Baseline type 2 diabetes had a significant association with elevated high sensitivity cardiac troponin T levels in Chinese community-dwelling population: a 5-year prospective analysis

Abstract: BackgroundThe present analysis was designed to investigate the association of type 2 diabetes (T2D) with high sensitivity cardiac troponin T (hs-cTnT) during the 5 years of follow-up, and explore which one of fasting blood glucose (FBG) and postprandial blood glucose (PBG) is a determinant of this association in Chinese community-dwelling population.MethodsThis prospective community-based analysis was conducted based on 730 participants without coronary artery disease and hs-cTnT values ≥14 pg/mL receiving two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
2
4
0
Order By: Relevance
“…Importantly, the patient had no history of renal impairment, cardiac disease, or diabetes. Recent studies, both cross-sectional and longitudinal, have highlighted the association between elevated hsTnT levels and diabetes mellitus, consistent with our findings ( 38 , 39 ). HsTnT has even been proposed as a predictor of incident diabetes ( 40 ).…”
Section: Discussionsupporting
confidence: 93%
“…Importantly, the patient had no history of renal impairment, cardiac disease, or diabetes. Recent studies, both cross-sectional and longitudinal, have highlighted the association between elevated hsTnT levels and diabetes mellitus, consistent with our findings ( 38 , 39 ). HsTnT has even been proposed as a predictor of incident diabetes ( 40 ).…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, a previous study by Fu et al (24) found a significant connection between type 2 diabetes and high hs-cTnT levels in models of multivariate logistic regression (p value < 0.05). In multivariate linear regression models, elevated levels of postprandial blood glucose (p < 0.05) rather than fasting blood glucose (p > 0.05) discovered the important relationship with higher hs-cTnT levels.…”
Section: Discussionsupporting
confidence: 68%
“…In this study, admission blood glucose level, age, and history of antiplatelet drug use were found to be risk factors for elevated troponin. Type 2 diabetes has been proven to have a significant association with elevated hs-cTnT levels in community-dwelling population; fasting blood glucose played a crucial role in this association [ 36 ]. Sharain et al studied 830 patients and found that older age was also associated with elevated hs-cTnT [ 37 ].…”
Section: Discussionmentioning
confidence: 99%